GGA2 interacts with EGFR cytoplasmic domain to stabilize the receptor expression and promote cell growth - Takefumi Uemura (Nature Portfolio, 2018)
Abstract Epidermal growth factor receptor (EGFR) signaling and its downregulation upon ligand binding have been extensively documented. However, the mechanisms by which cells maintain steady-state EGFR expression remain poorly understood. Here, we report a novel role of Golgi-localized, γ-adaptin ear-containing, ADP ribosylation factor-binding protein 2 (GGA2) in the control of EGFR turnover. Whereas GGA1- or GGA3-depletion increased EGFR expression, GGA2-depletion by RNAi greatly reduced steady-state expression of EGFR, reflecting enhanced lysosomal degradation of EGFR. Subsequent pull-down assays showed interactions of VHS-GAT domains from three GGAs with the cytoplasmic juxtamembrane region (jxt) of EGFR, which was dependent on N108 in the VHS domain. Proximity ligation assay also revealed the steady-state interaction between GGA2 and EGFR in situ. Moreover, reduced expression of EGFR in GGA2-depleted cells was reversed by additional depletion of GGA1 or GGA3, suggesting that GGA1 and GGA3 promote EGFR degradation. In addition, GGA2-depleted cells had reduced EGF signaling and cell proliferation in cell culture and xenograft experiments. Finally, GGA2 was upregulated in 30.8% of human hepatocellular carcinomas and 23.3% of colorectal cancers. Together, these results indicate that GGA2 supports cell growth by interacting with EGFR for sustaining the receptor expression.